1986
DOI: 10.1002/cne.902470206
|View full text |Cite
|
Sign up to set email alerts
|

Second somatic sensory cortical area (sii) in a prosimian primate, galago crassicaudatus

Abstract: The cortex adjacent to and along the upper bank of the lateral sulcus (UB-LS) of a prosimian primate, Galago crassicaudatus, was explored to determine the topographical representation of low-threshold cutaneous inputs to this region. The somatic sensory projections to this cortex were considered homologous to those defined in other species as the second somatosensory cortical area (SII). Multiple and single neuron recordings were obtained with tungsten microelectrodes in animals anesthetized with sodium pentob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
45
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 26 publications
8
45
1
Order By: Relevance
“…In mice, the localization of SII was discovered by Woolsey (1967) and the area was mapped by Carvell and Simons (1987). SII contains the entire body representation in a somatotopic map, but receptive fields are larger than in primary somatosensory area (Burton and Carlson, 1986;Carvell and Simons, 1987). It is reciprocally connected with the ipsilateral somatosensory (SI) and motor cortex (Carvell and Simons, 1987;Miyashita et al, 1994), ventral posterolateral (VPL), ventral posteromedial (VPM), and posterior (PO) nucleus of the thalamus (Burton and Kopf, 1984;Theyel et al, 2010), and the prefrontal cortex (Kostopoulos et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In mice, the localization of SII was discovered by Woolsey (1967) and the area was mapped by Carvell and Simons (1987). SII contains the entire body representation in a somatotopic map, but receptive fields are larger than in primary somatosensory area (Burton and Carlson, 1986;Carvell and Simons, 1987). It is reciprocally connected with the ipsilateral somatosensory (SI) and motor cortex (Carvell and Simons, 1987;Miyashita et al, 1994), ventral posterolateral (VPL), ventral posteromedial (VPM), and posterior (PO) nucleus of the thalamus (Burton and Kopf, 1984;Theyel et al, 2010), and the prefrontal cortex (Kostopoulos et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…There is compelling anatomical evidence from primates that S1 and S2 are reciprocally connected through extensive corticocortical projection neurons arising from superficial layers (I-III) (Friedman et al, 1980;Burton and Carlson, 1986;Pons and Kaas, 1986;Kandel et al, 2010). Importantly, both S1 and S2 receive direct projections from multiple thalamic nuclei such as the ventral posterior nucleus (VP) (including ventral posterior lateral and ventral posterior medial nuclei), the ventral posterior inferior nucleus (VPI), and the centrolateral nucleus (CL) (Jones and Leavitt, 1974;Burton and Jones, 1976;Friedman and Murray, 1986;Krubitzer and Kaas, 1992;Jones, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In the Asian prosimian Nycticebus, we reported a minor second glabrous projection within the major projection of the hairy hand to area 1 . Our subsequent studies of secondary somatic sensory cortex (SII) in Galago demonstrated a single hand and body projection pattern (Burton and Carlson, 1986) with features similar to the single area defined in SII of Macaca (Robinson and Burton, 1980). Like Macaca, the NW anthropoids Aotus (Merzenich et al, 1978), Cebus (Fellernan et al, 1983) and Saimiri (Sur et al, 1982) have separate projections from glabrous hand and other body surfaces in areas 3b and 1 (Fig.…”
mentioning
confidence: 71%
“…Eight adult Galago garnetti served as subjects in these studies (Table 1). This is the same species used in our previous studies of SI and SII and referred to as G&go crassicaudutus (Carlson and Welt, 1980;Burton and Carlson, 1986). The species designation of the greater Galago has changed over the past decade.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation